2022
DOI: 10.1155/2022/5644956
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Values of Laboratory Biomarkers in Predicting a Severe Course of COVID-19 on Hospital Admission

Abstract: Objective. We intend to identify differences in the clinicodemographic and laboratory findings of COVID-19 patients to predict disease severity and outcome on admission. Methods. This single-centred retrospective study retrieved laboratory and clinical data from 350 COVID-19 patients on admission, represented as frequency tables. A multivariate regression model was used to assess the statistically significant association between the explanatory variables and COVID-19 infection outcomes, where adjusted odds rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…18 Classic inflammatory indicators, including the white blood cell count and its subtypes, notably the neutrophil and lymphocyte counts, have a well-established place in clinical practice. 19,20 By combining these counts, the SIRI emerges as a comprehensive biomarker for evaluating the body’s inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
“…18 Classic inflammatory indicators, including the white blood cell count and its subtypes, notably the neutrophil and lymphocyte counts, have a well-established place in clinical practice. 19,20 By combining these counts, the SIRI emerges as a comprehensive biomarker for evaluating the body’s inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
“…These vary from vital parameters and measured laboratory tests, and demographic data to experimental biomarkers. [ 2 3 4 5 ] Also, in several studies, low blood oxygen saturation (SPO2) on admission has been reported as a strong predictor of hospitalization and mortality in COVID-19 patients. [ 6 7 8 9 10 ] Understanding changes in SPO2 outcome that may occur during hospitalization, assessing risk factors for this potential marker, and time to death outcome may improve diagnosis and management.…”
Section: Introductionmentioning
confidence: 99%